Organizational climate and employee engagement: A commercial bank perspective in Southeast Nigeria - Phina, Onyekwelu Njideka; Ogechukwuand, Nwogwugwu Ngozi; Shallom, Anizoba Adaeze (goodwood publishing, 2021)
Purpose: This study aimed to ascertain the role organizational climate could play in galvanizing the employees of commercial banks in southeast Nigeria for better performance through exhibiting greater engagement to their jobs and organizations. Research methodology: Survey Research Design was employed for the study. The study population consisted of 988 employees of 50 randomly selected commercial banks in the region studied. Data were elicited through a structured questionnaire while the analysis was carried out using Simple Regression Analysis and hypothesis tested at a 5% level of significance. Results: The findings showed that there is a statistically significant relationship between Distributive Justice Climate and Job Satisfaction in Microfinance Banks in South-East Nigeria (r = .962; R-Square = .926; F = 5865.689; p-value<.05) and that there is a statistically significant relationship existing between Open Communication Climate and Positive Meaning in Microfinance Banks in South-East Nigeria (r = .982; R-Square = .965; F = 13000.304; p-value<.05). Limitations: Because of the concentration of commercial banks in Anambra state, most of the banks selected for the study through a random method were from Anambra State. This could affect the generalizability of the findings. Contribution: This study contributed to the already existing body of knowledge on Organizational Climate and Employee Engagement. The study also revealed empirical results of the relationship between the variables of the study, specifically in commercial banks in South-East Nigeria.